Robotic hand controlled based on flexible sensor by glove using wireless communication - Dhilen, Manimaran (2022)
A humanoid robot's hand is a vital component. It's tough to create an action that looks like a human side. This study suggested a similar-sized and light-weight robotic hand and investigated the possibility of controlling based on flexible sensor by glove using wireless communication. The robotic hand is built to manoeuvre and function like a human hand. One of the robot hand's fingers has three degrees of freedom, nearly identical to a human finger. When the fingers of the manipulator switch, the glove using wireless communication sends a feedback signal to the microcontroller. Each robot hand's finger sector is powered by a Servo Motor chain drive. Furthermore, since the servo motor can only supply a low torque for the finger, the robot hand can only produce a force that is appropriate for each finger. Arduino Mega monitor the robot's entire behaviour and activity. The robot hand is managed in real time by the glove using wireless communication. As a result, it may perform tasks similar to those performed by a human hand, such as gripping an object. The robot hand will be used to implement humanoid robots with further research and development